Improved Biomass Cook Stoves for Climate Change Mitigation? : Evidence of Preferences, Willingness to Pay, and Carbon Savings - Dissanayake, Sahan T. M. (World Bank, Washington, DC, 2018)
This paper investigates household preferences for improved cook stoves using a choice experiment administered in rural Ethiopia, and the cost-effectiveness of an improved stove for reducing global greenhouse gas emissions. In Ethiopia, about 96 percent of household energy demand is fulfilled by biomass. Improved stoves use less firewood and produce less smoke, and they have been touted as a way to reduce greenhouse gas emissions and health effects from indoor air pollution, as well as to improve forest conservation. Although there are many studies on the adoption of improved stoves, there is limited information on the willingness to pay for particular attributes of stoves, information that is vital for designing effective stoves and improving stove adoption. The paper finds that households have a positive willingness to pay for the durability, fuelwood use reduction, smoke reduction, and cooking time reduction of improved stoves. It also shows that the stove used in this experiment can be cost-effective for reducing greenhouse gas emissions, which suggests that programs providing payments for reducing greenhouse gas emissions could strengthen stove adoption if they are well implemented. The main reason the stoves are not being adapted is the lack of availability, which is a key message to policy makers.